Analisis Faktor-Faktor yang Mempengaruhi Citra dan Pengaruhnya terhadap Word of Mouth pada Jasa Pendidikan - Riswono, Haliman Tjahyadhi (Jurnal Ilmiah Aset, 2010)
Buying service is relatively more risky than buying tangible product that can be evaluated in advance. An intangible character that cannot be sensed earlier is a typical quality of service product. Educational service that cannot be evaluated earlier is difficult to be estimated its risks, such as finance, time, psychology (emotionally uncomfort), functional and social. Therefore, under graduate students will look for more complete information through image of a college or either opinion leader or word of mouth. The research was carried out at Widya Manggala School of Economics whose image is not quite good in society. The data in this research was primary data, namely questionnaire distributed to 115 students of Widya Manggala School of Economics Semarang. The analysis technique used was Structural Equation Model (SEM) from software AMOS 7.0. Based on the data analysis, it can be concluded that the variable of service quality and educational fee had positive and significant influence toward the image, while the variable of image positively influence the variable of word of mouth.